Development of Innovation and the Role of Human Capital in Good Corporate Governance in Improving Company Performance PT. Kilang Pertamina International RU VI Balongan - Sadiva, Nadya Vallerie; Wulanda, Berlian Zelliscia; Dwinanda, Viana; Hartono, Edy (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to examine the influence of innovation, human capital and good corporate governance on company performance. This research uses quantitative research methods. The sampling technique is a sampling technique of 5% of the existing population. The sample used was 83 employees of the company PT. Kilang Pertamina International RU VI Balongan. Data collection was obtained from distributing questionnaires and making direct observations at the company. Based on the research results, it shows that innovation has a significant effect on company performance, human capital has a significant effect on company performance and good corporate governance has a significant effect on PT company performance. Pertamina International RU VI Balongan Refinery.